Experimental Detection of the Intrinsic Difference in Raman Optical Activity of a Photoreceptor Protein under Preresonance and Resonance Conditions. (23rd July 2015) - Haraguchi, Shojiro; Hara, Miwa; Shingae, Takahito; Kumauchi, Masato; Hoff, Wouter D.; Unno, Masashi
Abstract Raman optical activity (ROA) is an advanced technique capable of detecting structural deformations of light‐absorbing molecules embedded in chromophoric proteins. Resonance Raman (RR) spectroscopy is widely used to enhance the band intensities. However, theoretical work has predicted that under resonance conditions the ROA spectrum resembles the shape of the RR spectrum. Herein, we use photoactive yellow protein (PYP) to measure the first experimental data on the effect of changing the excitation wavelength on the ROA spectra of a protein. We observe a close similarity between the shape of the RR spectrum and the resonance ROA spectrum of PYP. Furthermore, we experimentally verify the theoretical prediction concerning the ratio of the amplitudes of the ROA and Raman spectra. Our data demonstrate that selecting an appropriate excitation wavelength is a key factor for extracting structural information on a protein active site using ROA spectroscopy.